Mối quan hệ giữa hiệu quả hoạt động và cấu trúc vốn của các doanh nghiệp tại Việt Nam - Ly Phuong , Thuy; Vuong Quoc , Duy; Pham Le , Thong (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This study determines the simultaneous impacts between capital structure and efficiency of enterprises by using the three-stage least squares (3SLS) regression technique associated with firm fixed effects estimation. This analysis utilizes the panel data of 19,453 enterprises forming into 33,415 observations in agriculture, forestry and aquaculture; manufacturing; construction; and real estate sectors. These data are collected from the Vietnam Enterprise Surveys conducted by the General Statistics Office during 2010–2017 period. The estimation results show that there are simultaneously significant effects between efficiency and capital structure of the firms. Enterprises with higher leverage are likely to gain higher profitability; on a other hand, the impact of leverage on efficiency is characterized by an inverted U shape. In addition, firm-specific efficiency level is found to be dependent on tangible assets, age, size, and ownership structure of the firms while capital structure is dependent on tangible assets, asset features, non-debt tax shields, size and ownership structure.
Keywords: Enterprise; Efficiency; Capital structure; Vietnam; 3SLS